Paying for risk: Bankers, compensation, and competition - Simone M. Sepe; Charles K. Whitehead (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
Efforts to control bank risk address the wrong problem in the wrong way. They presume that the financial crisis was caused by CEOs who failed to supervise risk-taking employees. The responses focus on executive pay, believing that executives will bring non-executives into line - using incentives to manage risk-taking - once their own pay is regulated. What they overlook is the effect on non-executive pay of the competition for talent. Even if executive pay is regulated, and executives act in the bank's best interests, they will still be trapped into providing incentives that encourage risk-taking by non-executives due to the negative externality that arises from that competition. Greater risk-taking can increase short-term profits and, in turn, the amount a non-executive receives, potentially at the expense of long-term bank value. Non-executives, therefore, have an incentive to incur significant risk upfront so long as they can depart for a new employer before any losses materialize. The result is an upward spiral in compensation - reducing an executive's ability to set non-executive pay and the ability of any one bank to adjust compensation to reflect risk-taking and long-term outcomes. New regulation must address the tension between compensation and competition. Regulators should take account of the effect of competition on market-wide levels of pay, including by non-banks who compete for talent. The ability of non-executives to jump from a bank employer to another financial firm should also be limited. In addition, banks should be required to include a long-term equity component in non-executive pay, with subsequent employers being restricted from compensating a new employee for any losses she incurs related to her prior work.
Keywords: 330